PERENCANAAN MODUL PEMBELAJARAN IPS PADA KURIKULUM MERDEKA BELAJAR TAHUN PELAJARAN 2023/2024 - Saputri, Meisy Naha; Suriyanti, Yulia; Thoharudin, Munawar (STKIP Persada Khatulistiwa Sintang, 2025)
The background of this research is the lack of development in compiling social studies teaching modules on the independent curriculum. This study aims to describe the making of modules in social studies learning as an implementation of the independent learning curriculum at SMP Negeri 6 Satu Atap Sintang in the 2023/2024 academic year. This study uses a qualitative approach with descriptive methods with observation, interview, and documentation data collection techniques as data analysis techniques. Research instrumentation observation sheets, interview sheets, and documents. The subject of this research is the social studies teacher at SMP Negeri 6 Satu Atap Sintang for the 2023/2024 academic year. The results of this study indicate that the making of teaching modules in the independent curriculum at SMP 6 Satu Atap Sintang is successful with learning outcomes that are in accordance with student needs, compiling interesting learning activities, developing modules independently, interactively, effective evaluation, accommodating student interests and needs, and additional support to students and the participation of parents to support learning at home. In this study, the writer hope that further research can correct deficiencies and can develop new research based on the results of this study.